Study of Subsonic Flow Over a TOW 2B Missile. Issue 1 (2nd January 2016) - Goudarzi, Koorosh; Jamali, Mehdi
Abstract : The objective of this investigation is to study the subsonic flow over a missile. In this paper, a model of TOW 2B missile is studied. Two computational approaches are being explored, namely solutions based on the Reynolds-averaged compressible Navier-Stokes equations and solutions based on the inviscid flow (small disturbance theory). The simulations are performed at the Mach number of 0.6, 0.7, 0.8, 0.9 and 1.0 at four angles of attack of 2, 4, 6 and 8 degree. Results obtained from analytical simulation are compared with numerical data. It is found that lift and drag coefficients would go up by increasing of the angle of attack and the Mach number. Trend of changes of the results that obtained from the small disturbance theory is roughly as same as the numeric solution.